Sexual Dimorphism and Clinical Relevance of Thickness and Angulation of Lateral Lamella of Cribriform Plate-A Multidtector Computed Tomographic Study - Anandagouda V Naikanur; Balappa M Bannur; Manjula Patil; Sanjeev I Kolagi (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: The aim of this study was to establish the morphometry and sexual dimorphism of laterallamella of cribriform plate in the North Karnataka region.Method: Six hundred and forty four (644) Multidetector computed tomographic scans were collectedfrom North Karnataka region and analyzed by using RadiAnt DICOM Viewer. The thickness andangulation of lateral lamella of cribriform plate of olfactory fossa were calculated on both the sides inboth genders. Statistical analysis was done by using Student unpaired‘t’ test.Conclusion: There was statistically significant difference in the angle of lateral lamella of cribriformplate when compared between right side (mean=106.25˚) and left side (mean=109.38˚) in males.There was no such difference among females. Statistically significant difference was observed in theangle of lateral lamella of cribriform plate in male patients (mean=106.25˚) when compared to femalepatients (mean=109.61˚). The thickness of lateral lamella of cribriform plate was not significant whencompared between two sides in males and females. Hence, these variations in the morphometry of thelateral lamella of cribriform plate of ethmoid bone will be of importance for the surgeons in Functionalendoscopic sinus surgeries and anterior skull base surgeries.